MANAJEMEN BIAYA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - HIMYAR PASRIZAL (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Schooled cost management effectively and efficient constitute activity something that essential in order to education upgrade. The aims of state to smarten up nation life will be reached along with be reached intent schooled and student individual which is get education and up to achievement which at the farthest. In order to intent attainment with that with upgrade education therefore has to be backed up by finance that is equal to of all party as one be worded in UU RI No.20 Year 2003, about National Education System, which is education Finance becomes to carry the ball with among Government, Local government, and society. Beside it also schooled finances source shall determine to base justice principle, sufficiency, and sustainability.Key words: Manajemen biaya, mutu pendidikan